Analisis Strategi Pendapatan dalam Meningkatkan Kesejahteraan Masyarakat Nelayan - Joedy Andrian; Arsa Arsa; Fauzan Ramli (JURNAL RISET MANAJEMEN (JURMA), 2024)
This thesis is entitled "Strategy analysis in improving the welfare of fishing communities (study of Kuala Tungkal fishermen". Strategy analysis is a process to help fishermen achieve their goals. The problems in this research are (1) what is the strategy to increase the income of fishing communities? (2 ) What is the condition of the economic welfare of the fishing community in Kuala Tungkal? This research aims to find out the strategies of Kuala Tungkal fishermen to improve the welfare of the fishing community. The research method used is a qualitative method through primary data then the tools for data collection used are interviews, observation, and documentation Data analysis is qualitative descriptive by means of data reduction, data presentation and conclusions.